2015
DOI: 10.1016/j.physa.2014.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salt concentration on the stability of heterogeneous DNA

Abstract: We study the role of cations on the stability of double stranded DNA (dsDNA) molecules.It is known that the two strands of double stranded DNA(dsDNA) have negative charge due to phosphate group. Cations in the form of salt in the solution, act as shielding agents thereby reducing the repulsion between these strands. We study several heterogeneous DNA molecules. We calculate the phase diagrams for DNA molecules in thermal as well as in force ensembles using Peyrard-Bishop-Dauxois (PBD) model. The dissociation a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…The stability of double stranded DNA (dsDNA) can be affected by temperature, pH and ionic composition of solution (solvent)[19]. Salting-out has proven to be a cost-effective method for extracting DNA from whole blood, which gives good DNA yield for downstream analyses[20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The stability of double stranded DNA (dsDNA) can be affected by temperature, pH and ionic composition of solution (solvent)[19]. Salting-out has proven to be a cost-effective method for extracting DNA from whole blood, which gives good DNA yield for downstream analyses[20,21].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in somatic cells the concentrations of sodium ions substantially increase during activation to become cancer cells [1,52]. From most of the previous studies it was concluded that these cations contribute to the stability of the DNA in the cell [28,33]. These cations act as shielding agents for the negatively charged strands of DNA.…”
Section: Discussionmentioning
confidence: 99%
“…For the current investigations we adopt the standard Peyrard Bishop Dauxois (PBD) model [26,27] and modify the potentials appearing in the model. In our earlier work, we showed that the PBD model has enough detail to explain the thermal as well as mechanical stability of DNA molecules at lower strengths of salt and with varying salt concentration [5,28]. Our presentation in the current manuscript is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…The sequence heterogeneity has effect on the stacking interaction along the strand. This can be taken care of through the single strand elasticity parameter k. One can take the variable k according to the distribution of bases along the strand [31]. A defect in a pair will modify the electronic distribution around the bases hence the stacking parameters.…”
Section: The Modelmentioning
confidence: 99%